2018
DOI: 10.1002/jat.3735
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomics analysis of kidneys in rats administered with chronic low‐dose cadmium by ultra‐performance liquid chromatography‐mass spectrometry

Abstract: This study aimed to investigate the nephrotoxicity in rats administered with chronic low‐dose cadmium (Cd) by ultra‐performance liquid chromatography‐mass spectrometry. A total of 40 male Sprague‐Dawley rats were randomly assigned to four groups, namely: control; low‐dose (0.13 mg/kg·body weight [bw]); middle‐dose (0.80 mg/kg·bw); and high‐dose (4.89 mg/kg·bw). The rats received CdCl2 daily via drinking water for 24 weeks. Rat kidneys were collected for metabonomics analysis. Principal components analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…Two other significantly different metabolites were hypoxanthine nucleoside (M251T217) and hypoxanthine (M135T286). Hypoxanthine nucleoside was one of nucleoside compounds based on hypoxanthine, which was obtained from the reaction of adenosine with nitrous acid or enzymatic ammonolysis (Zhang et al, 2018). Hypoxanthine was produced under the action of nucleoside phosphate carboxylase.…”
Section: Metabolomics Resultsmentioning
confidence: 99%
“…Two other significantly different metabolites were hypoxanthine nucleoside (M251T217) and hypoxanthine (M135T286). Hypoxanthine nucleoside was one of nucleoside compounds based on hypoxanthine, which was obtained from the reaction of adenosine with nitrous acid or enzymatic ammonolysis (Zhang et al, 2018). Hypoxanthine was produced under the action of nucleoside phosphate carboxylase.…”
Section: Metabolomics Resultsmentioning
confidence: 99%
“…Tetranor 12-HETE as a kind of oxylipin with pro-inflammatory properties, has been documented to participate in the inflammatory response and accelerate the progression of HTN ( 27 ). Previously, it was reported that the abundance of Tetranor 12-HETE was promoted by high-dose cadmium intervention, which elicited nephrotoxicity and oxidative stress to the kidneys ( 28 ). Meanwhile, Li Q and colleagues demonstrated that plasma level of Tetranor 12-HETE was extremely elevated in patients suffering from nonalcoholic fatty liver disease ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics analyzes the changes of the total metabolites of biological samples affected by the environment. This helps to understand how animals and plants respond to various hostile factors at the molecular level [ 6 ]. At present, it is widely used in the study of environmental pollutants, such as investigating the mechanism of Cd poisoning in rat urine [ 7 ] and kidneys [ 6 ], which provides the possibility for directly evaluating the health effects of low-dose environmental poisons [ 8 ].…”
Section: Introductionmentioning
confidence: 99%